Encyclopedia of Hydrological Sciences 2005
DOI: 10.1002/0470848944.hsa190
|View full text |Cite
|
Sign up to set email alerts
|

Teleconnections in the Earth System

Abstract: This article illustrates the large‐scale connectivity of the atmosphere–ocean coupled system and generalizes the concept to regional scales and to other components of the earth system. Connections at a distance, or teleconnections, can occur by the direct transfer of mass by changes in regular circulations or by propagating waves initiated by a variety of mechanisms. Questions as to what extent recognized teleconnection patterns can be associated with identifiable forcing mechanisms, to what extent these patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…Teleconnection patterns in atmospheric and climate sciences, refer to quasiperiodic and persistent anomalies in the atmospheric pressure and circulation pattern that span over large geographical areas (Nigam ; Chase et al ). These patterns are primarily outcomes of the internal dynamics in the atmosphere although some teleconnection patterns have been shown to be sensitive to particular sea surface temperatures.…”
Section: Study Site and Backgroundmentioning
confidence: 99%
“…Teleconnection patterns in atmospheric and climate sciences, refer to quasiperiodic and persistent anomalies in the atmospheric pressure and circulation pattern that span over large geographical areas (Nigam ; Chase et al ). These patterns are primarily outcomes of the internal dynamics in the atmosphere although some teleconnection patterns have been shown to be sensitive to particular sea surface temperatures.…”
Section: Study Site and Backgroundmentioning
confidence: 99%
“…strong statistical relationships between weather in different parts of the world, in the climate system are associated with the large-scale circulation of the atmosphere and the oceans. In the atmosphere, climate signals can be transferred to regions far from the physical source of the variability, while in the oceans teleconnections are associated with the global thermohaline circulation (e.g., Chase et al, 2005). Tree rings, with their large spatial coverage and high resolution, are highly useful proxies for studies of spatiotemporal stability of observed climate patterns, and associated teleconnections.…”
Section: Teleconnectionsmentioning
confidence: 99%
“…ENSO is an interannual oscillation (2-7 years - Trenberth and Hurrell 1994;Cane 2005;McPhaden et al 2006) composed of two active phases, El Niño and La Niña, whose main signatures are observed through sea surface temperature (SST) variations in the central and eastern equatorial Pacific waters (Chase et al 2006). El Niño is associated with anomalously warm waters, and La Niña with anomalously cold waters.…”
Section: Introductionmentioning
confidence: 99%